Mine Wastes Characterization, Treatment and Environmental Impacts - Lottermoser, Bernd (Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book is not designed to be an exhaustive work on mine wastes. It aims to serve undergraduate students who wish to gain an overview and an understanding of wastes produced in the mineral industry. An introductory textbook addressing the science of such wastes is not available to students despite the importance of the mineral industry as a resource, wealth and job provider. Also, the growing imp- tance of the topics mine wastes, mine site pollution and mine site rehabilitation in universities, research organizations and industry requires a textbook suitable for undergraduate students. Until recently, undergraduate earth science courses tended to follow rather classical lines, focused on the teaching of palaeontology, cryst- lography, mineralogy, petrology, stratigraphy, sedimentology, structural geology, and ore deposit geology. However, today and in the future, earth science teachers and students also need to be familiar with other subject areas. In particular, earth science curriculums need to address land and water degradation as well as rehabili- tion issues. These topics are becoming more important to society, and an increasing number of earth science students are pursuing career paths in this sector. Mine site rehabilitation and mine waste science are examples of newly emerging disciplines. This book has arisen out of teaching mine waste science to undergraduate and graduate science students and the frustration at having no appropriate text which documents the scienti?c fundamentals of such wastes.